2013
DOI: 10.1002/jsfa.6084
|View full text |Cite
|
Sign up to set email alerts
|

Overproduction of a thermostable 4‐α‐glucanotransferase by codon optimization at N‐terminus region

Abstract: The codon-optimized TTαGT that was produced in a GRAS microorganism, B. subtilis, without the selection antibiotics is potentially useful in the food industry as a food-grade enzyme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Studies have shown that in E . coli if rare codons occur near the 5’ end of an ORF, especially as clusters, the effect can be detrimental, resulting in very low to no expression of foreign genes [ 20 , 48 , 49 , 50 , 51 , 52 ]. By inserting the rarest codon AGA Arg at different positions near the 5’ end of a gene Kim and Lee [ 20 ] reported that positioning at the +2 and +3 positions had the most negative effect.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that in E . coli if rare codons occur near the 5’ end of an ORF, especially as clusters, the effect can be detrimental, resulting in very low to no expression of foreign genes [ 20 , 48 , 49 , 50 , 51 , 52 ]. By inserting the rarest codon AGA Arg at different positions near the 5’ end of a gene Kim and Lee [ 20 ] reported that positioning at the +2 and +3 positions had the most negative effect.…”
Section: Discussionmentioning
confidence: 99%
“…The recombinant E. coli cells were cultured overnight at 37°C in Luria-Bertani broth [1% (w/v) Bacto-tryptone, 0.5% (w/v) yeast extract, and 0.5% (w/v) NaCl] supplemented with kanamycin (20 lg/mL). Production of the codon-optimized TTaGT (previously termed TTaGT-mut6) was carried out as described previously [16]. The protein concentration was determined according to the method of Bradford [19], using bovine serum albumin as a standard.…”
Section: Methodsmentioning
confidence: 99%
“…Using an Escherichia coli-B. subtilis shuttle vector equipped with a strong promoter, a thermostable aGTase from Thermus thermophilus (TTaGT) was successfully produced in B. subtilis [16]. Because aGTases are originally cytoplasmic proteins, the recombinant TTaGT in B. subtilis existed in the cytoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…α-GTase transglycosylation activity is useful in carbohydrate chemistry. Starches that are modified by α-GTases show novel rheological and nutritional properties, such as thermoreversible gelation, fat-replacing properties, and hypocholesterolemic and hypoglycemic effects [9]. α-GTases from different bacteria have successfully modified the properties of various food materials, including increased water solubility, stability, functional effects, and taste [10].…”
Section: Introductionmentioning
confidence: 99%
“…α-GTases from different bacteria have successfully modified the properties of various food materials, including increased water solubility, stability, functional effects, and taste [10]. In addition, intramolecular glucan transferase produces cyclic glucans (cycloamyloses) with a higher degree of polymerization compared with cyclodextrins [9]. 1-Deoxynojirimycin (DNJ), an aza-sugar, has structural characteristics similar to those of cyclic monosaccharides; however, the oxygen is substituted with a nitrogen atom.…”
Section: Introductionmentioning
confidence: 99%